Global, diffuse and direct solar radiation at the surface in the city of Rio de Janeiro: Observational characterization and empirical modeling - Marques Filho, Edson P.; Oliveira, Amauri P.; Vita, Willian A.; Mesquita, Francisco L. L.; Codato, Georgia; Escobedo, Joao F. [UNESP]; Cassol, Mariana; Franca, Jose Ricardo A. (Elsevier B.V., 2016)
The city of Rio de Janeiro and others 18 cities compose the Metropolitan Area of Rio de Janeiro. The main objective of this work is to characterize observationally the diurnal and seasonal evolution of the solar radiation components in the city of Rio de Janeiro. The measurements of global and diffuse solar radiation and standard meteorological variables at the surface have been carried out regularly at the Geo-science Institute of Federal University of Rio de Janeiro since October of 2011. The microclimatic conditions show that the period 2011-2014 was warmer during most of the year and drier in summer and spring in comparison with climate normal. All solar radiation components present a well defined diurnal cycle with maximum at noon. The estimates of global and direct solar radiation indicate a great potential available for solar energy at the surface, particularly in summer. The behavior of the clearness index and diffuse solar radiation fraction is similar in summer and winter. The Angstrom formula represents properly the estimate of the monthly average daily value of global solar radiation. The sigmoid logistic function is statistically more significant in comparison with others correlation models to represent the diffuse fraction as a function clearness index. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Solar radiation components; Rio de Janeiro; Local climate conditions; Diffuse solar fraction model